Characteristics and risk factors of snoring and the prevalence of suspected obstructive sleep apnea in children - Bambang Supriyatno; Rusmala Deviani; Alan R Tumbelaka; Evita KB Ifran; Nastiti N Rahajoe (Paediatrica Indonesiana, 2005)
Background Snoring as a consequence of upper airway obstruc-tion is common in children. Snoring can be considered as normal,but might also reflect a disease such as obstructive sleep apnea(OSA), which is associated with serious morbidities. In Indonesia,data on the characteristics and risk factors of snoring and obstruc-tive sleep apnea is limitedObjectives The aims of this study were to find out the character-istics and risk factors of snoring in children and to determine theprevalence of suspected OSA in snoring children.Methods A cross-sectional study was carried out on children aged5-13 years using parental questionnaires scored according to theBrouilette formula. All children underwent physical examination forweight, height and tonsil size. Adenoid radiology was performedon part of the samples.Results Of the 917 questionnaires distributed, only 658 were com-pleted. The ratio of boys to girls was equal. Obesity was detectedin 18.3% of children, among whom 54.2% snored. Obese childrenwere 2.1 times more likely to snore. Besides obesity, rhinitis andatopy were found to be associated with snoring (PR= , 95%CI ;and PR= , 95%CI ; respectively). Asthma and tonsil hypertrophywere shown not to be predisposing factors of snoring. Childrenwith adenoid hypertrophy were 1.8 times more likely to snore ha-bitually. The prevalence of snoring and suspected OSA in childrenaged 5-13 years were 31.6% and 5.9%, respectively.Conclusion Risk factors of snoring were obesity, adenoid hyper-trophy, atopy and rhinitis. Prevalence of snoring in children age 5-13 years was 31.6% and that of suspected OSA cases was 5.9%.